2021
DOI: 10.1186/s12904-021-00721-6
|View full text |Cite
|
Sign up to set email alerts
|

Dignity of informal caregivers of migrant patients in the last phase of life: a qualitative study

Abstract: Background A key aim of palliative care is to improve the quality of life of patients and their families. To help ensure quality of life for the families of patients with migrant backgrounds, this study sought insights into the dignity of informal caregivers in migrant communities. This could improve understanding of family-centered care for migrant patients. Methods Twenty semi-structured interviews with informal caregivers of Turkish, Moroccan, o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In addition, we found that reflecting about dignity of patients is intertwined with experienced dignity of family members. This was earlier found in research on migrant patients' informal caregivers which indicated that when health care jeopardised the dignity of their loved one, it affected their dignity as well and vice versa [37]. Being cut off, ill-informed and not included in the care and medical decisions might have hindered both the experienced dignity of the dying person and the dignity of the relative.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, we found that reflecting about dignity of patients is intertwined with experienced dignity of family members. This was earlier found in research on migrant patients' informal caregivers which indicated that when health care jeopardised the dignity of their loved one, it affected their dignity as well and vice versa [37]. Being cut off, ill-informed and not included in the care and medical decisions might have hindered both the experienced dignity of the dying person and the dignity of the relative.…”
Section: Discussionmentioning
confidence: 81%
“…Being cut off, ill-informed and not included in the care and medical decisions might have hindered both the experienced dignity of the dying person and the dignity of the relative. This underlines that besides interactions with care professionals, relational interactions with relatives can form a powerful counter force for situations in which experienced dignity at the end of life is undermined through illness or circumstances of professional care [37].…”
Section: Discussionmentioning
confidence: 99%